MENGHADAPI FREE FLOW LABOUR SKILLED PERDAGANGAN BEBAS ASEAN : STUDI KASUS KABUPATEN BANYUMAS - Tundjung Linggarwati; Renny Miryanti (Jurnal Ilmu Politik dan Pemerintahan, 2011)
The world will coming to the liberalization of  flow of information, goods, capital, and labour. Information will travel everywhere without any borders. Goods will go to where they are best sold. Capital will flow to where its rate of return is the highest. Labour will work where he/she gets the most desirable (financial and non-financial) job.  If ASEAN Free Trade Area is successful in liberating trade and investments, the next step would be the effort to liberate the labour flow; skilled labour or unskilled labour.  This article attempts to describe the condition of labour force in Banyumas Region in Central Java Province, and the effort of the Local Government of Banyumas Region in increasing the quality of labour forces in facing free flow skilled labour of ASEAN Free Trade Area especially ASEAN Economic Community 2015.